Immunophenotypic and cytogenetic characteristics of pediatric acute lymphoblastic leukemia: A burden estimation study from Eastern India - Subhajit Dey Sarkar; Dipshikha Maiti; Apurba Ghosh; Mimi Ganguly; Nazneen Ahmed (Wolters Kluwer Medknow Publications, 2024)
Background: Acute lymphoblastic leukemia (ALL) is the most common childhood cancer. Immunophenotype (IPT) and cytogenetics are essential for diagnosis, risk stratification, and management for ALL. Objectives: Evaluating the burden of immunophenotypic and cytogenetic profile of pediatric ALL patients. Materials and Methods: A descriptive cross-sectional study was conducted on 100 patients of ALL (1-18 completed years) attending a tertiary-care center in Kolkata, Eastern India. Results: Ninety-six percent of patients had B-cell ALL (94.00% pre-B ALL and 2.00% Pro-B ALL) and 4.0% had T-ALL. 60% B-cell ALL were CD19/CD10 positive, 10% were CD79a positive, 9% were only CD19 positive, and 7% were only CD10 positive. Thirty-three percent of T-ALL were CD3+, whereas 22% were positive each for CD4 and CD7. 51.0% of patients had diploid, 46.0% hyperdiploid, and 3.0% hypodiploid karyotype. Among hyperdiploids, 98% had good prednisolone response and 89% had measurable residual disease (MRD) <0.01. Conclusion: The most commonly diagnosed ALL by IPT was pre-B ALL. Among the detectable cytogenetic abnormalities, t(12; 21) ETV6-RUNX1 was the most common. ZNF-384 gene arrangement was also detected in our study. t(12;21) ETV6-RUNX1 had a good treatment response, while t(9;22) BCR-ABL, t(1;19) TCF3-PBX1, iAMP-21, MLL gene rearrangement, and ZNF-384 gene arrangement had poor treatment response in terms of MRD.